Cryopyrin-associated periodic syndrome: a treatable genetic inflammatory condition. Issue 5 (10th June 2021) - Christensen, Maja; Wallis, Mathew; Jessup, Peter; Lemelle, Irène; Jones, Dean L
Abstract : A 20-year-old man presented with recurrent subdural haemorrhages on a background of progressive sensorineural hearing loss, juvenile idiopathic arthritis and intracranial hypertension of unknown cause. His mother had a similar previous history. They both had a persistently mildly elevated serum C reactive protein. Repeat lumbar punctures identified persistently elevated intracranial pressure and mild pleocytosis. A dural biopsy showed necrotising pachymeningitis with granulomatous vasculitis. The underlying cause in both patients was a cryopyrin-associated periodic syndrome. We discuss its varied phenotype and how clinicians need to be aware of this treatable genetic condition to facilitate early treatment and to prevent accumulation of disability.